Operational Excellence of Hydro Power Plant With “G-Action Mobile” - Arry Erawan; Wahyu Kurnia; Muhammad Nur Muharramsyahputra (Departemen Teknik Mesin dan Industri, Universitas Gadjah Mada, 2023)
The Gunung Wugul Mini Hydro Electric Power Plant (MHEPP) is a run of river power plant with a Commercial Operation Date (COD) of December 3, 2021, by PT PLN UP2D Central Java-Special Region of Yogyakarta. The application of corporate culture and regulations to run the operations of the Generating Unit such as asset management, Occupational Health and Safety Management System (SMK3) and Security Management System (SMP) require a high level of effort. Socialization and implementation related to the management of the Generating Unit must be carried out to the lowest level for the realization of good management. Focusing on Operational Excellence built on Shingo House Method, where elements of organizational leadership focus on the application of principles, systems, and tools to build superior performance factors by making continuous improvements. The implementation of G-Action Mobile optimizes digital technology and supports the company's program, namely digital transformation for control operations, maintenance, security, and Occupational Health and Safety (OHS) activities more effectively. The G-Action Mobile application can encourage the acceleration of the implementation of corporate culture within the Gunung Wugul MHEPP so that the achievement of a capability factor of 67.16% of the 33.60% target, the issuance of a Zero Accident decree, and the implementation of a security management system that is tight enough to support environmental conditions that can improve unit performance with conditions comfortable and safe.